Navigating human environment interaction in workplace dynamics for sustainable employee wellbeing: the role of organizational injustice, cynicism, and innovation in climate-adaptive organizations - Juanmei, Zhou; Tariq, Muhammad Numan; Sair, Shrafat A.; Sohail, Aamir (Frontiers in Human Dynamics, 2025)
IntroductionThis study examines the impact of human–environment interaction within organizational settings on sustainable employee well-being. It particularly focuses on how organizational injustice and cynicism hinder employee outcomes, and explores the potential of innovative culture and employee innovative behavior as mitigating and moderating factors, respectively.MethodsA total of 300 employees from climate-adaptive manufacturing firms in Beijing were surveyed. The study employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to test both direct and indirect relationships among key constructs including organizational injustice, cynicism, innovative culture, employee innovative behavior, and employee well-being.ResultsFindings reveal that innovative culture significantly contributes to employee well-being and mediates the negative effects of organizational injustice and cynicism. Additionally, employees’ innovative behavior positively moderates the relationship between organizational stressors and well-being, reflecting the role of innovation in enhancing employee resilience.DiscussionThe results highlight the importance of fostering a fair, innovation-driven organizational environment to promote psychological sustainability and well-being.